Real convergence in Central and Eastern European EU Member States: which role for exchange rate volatility? - Olga Arratibel; Davide Furceri; Reiner Martin (European Central Bank (ECB), 2008)
This paper analyzes the relation between exchange rate volatility and several macroeconomic variables, namely real per capita output growth, the credit cycle, the stock of inward foreign direct investment (FDI) and the current account balance, in the Central and Eastern European EU Member States. Using panel estimations for the period between 1995 and 2006, we find that lower exchange rate volatility is associated with higher growth (for relatively less financially developed economies), higher stocks of FDI (for relatively more open economies), higher current account deficits, and a more volatile development of the credit to GDP ratio.
Keywords: F3; F4; F5; 330; Catching-up; Convergence; credit; current account; EU; Exchange rate volatility; FDI; Growth; Wechselkurs; Wechselkurspolitik; Volatilität; Wirtschaftswachstum; Auslandsinvestition; Außenwirtschaftliches Gleichgewicht; Kreditmarkt; Politikkonvergenz; EU-Mitgliedschaft